Education as hospitality - re-thinking the 'educational' in education - Varpanen, Jan (Ethics and education, 2025)
A key question in the field of educational theory is the question of what is 'educational' in education. Responses to this question in the field are often connected to some type of change that is to take place in the child: children are socialised, they become subjects, or learn. I argue that this way of understanding what is educational in education is not applicable to a specific type of educational practice, which I label as co-existential practices. Co-existential practices are often taken up by educators, but to understand what is educational in them, we need an understanding that does not rely on references to changing children. I build an alternative view of education with the help of Derrida's concept of hospitality. I show how this interpretation of what is educational in education may help the field of educational theory to develop a fuller understanding of the relation between ethics and education.